Conceptualizing the integration of business and private components in individual information systems - Julia Lanzl; Henner Gimpel; Patrick Jürgen Afflerbach; Henner Gimpel (Schmalenbach Journal of Business Research (SBUR), 2024)
Individuals build their individual information system (IIS) with which they manage the boundary between different domains of life. In this age of permanent mobile accessibility, however, the boundary between the private and business domains can become blurred. While some users try to maintain a degree of separation between the two IIS sub-systems (the private and the business information system), others integrate them. Understanding such integration is essential as it affects wellbeing and performance in both domains. To further this understanding, we introduce a conceptualization of IIS that distinguishes between four layers of IIS: devices, digital identities, relationships, and information. To measure IIS integration, we develop a method based on the IIS components' usage frequencies in each domain.We evaluate our conceptualization as well as our measurement method by empirically testing a theoretical model of IIS integration on multiple layers. Our data provides empirical support for the importance of relationship integration as one of the four layers. This leads us to the conclusion that even though IIS are composed of four layers, only the relationship layer is of interest regarding IIS integration. Our results are of interest and service to individuals, organizations, and IT designers who aim to manage IIS integration for individual and organizational benefits.
Keywords: 650; Individual information systems; Boundary theory; IIS integration; Structural equation modeling